An Adaptive, real-time speech hiding system using high-capacity steganography techniques applied in innocuous music streams - Tablang, Martin Leandro C.
In conventional practice, a speech communication system encrypted with a strong cryptography algorithm produces a sufficiently secure channel - albeit a very noisy one. When transmissions are repeated extensively, the noisy nature of this channel can become very suspicious to attackers, resulting in increased vulnerabilities to attacks. To account for this problem, a covert communication system that masks the speech signal within an innocuous music stream - created through the use of high-capacity steganography techniques - is developed. We propose a novel real-time speech hiding system that combines and adjusts which steganography, cryptography, and compression techniques to use based on the usage requirements of the communication. Confidentiality of the secret signal, maximum data capacity, and robustness against attacks cannot be all optimized at the same time, so system parameters are adjusted in a case-to-case basis depending on what is most important in a specific occasion. Using a UDP-based audio streaming channel as a disguise, either an algorithmically composed sound or an uncompressed music file is played as cover medium for the secret speech channel. The result is a secure steganographic audio system that can encode as high as 442.99 kbps of secret data when data capacity is optimized, and be resilient enough to withstand up to 36 decibels of noise attacks when robustness of the message is prioritized, all while maintaining perceptual and statistical noise to indiscernible levels.